Russian-English dictionary of the mathematical sciences - by A.J. Lohwater with the collaboration of S.H. Gould, under the joint auspices of the National Academy of Sciences of the USA, the Academy of Sciences of the USSR, the American Mathematical Society. (American Mathematical Society, 1961)
"Publication of the English-Russian half ... [was] undertaken by the Soviet Academy of Sciences [under the title: Anglo-russkii slovar matematicheskikh terminov]